Leveraging Genomic Data in Smoking Cessation Trials in the Era of Precision Medicine: Why and How. Issue 4 (12th May 2017) - Chen, Li-Shiun; Zawertailo, Laurie; Piasecki, Thomas M; Kaprio, Jaakko; Foreman, Marilyn; Elliott, Hannah R; David, Sean P; Bergen, Andrew W; Baurley, James W; Tyndale, Rachel F; Baker, Timothy B; Bierut, Laura J; et al.
Abstract: In an era of Precision Medicine, it is vital to collect biological data within clinical trials and to integrate their analysis within the outcomes of the trial. The identification of genomic biomarkers that affect treatment response to smoking cessation treatment, both pharmacological and behavioral, or susceptibility to medication-related adverse reactions, holds real promise to improve treatment efficacy and to tailor the treatment approach to the individual. However, a clear challenge in identifying reliable biomarkers is in obtaining adequate sample sizes. Consortium-based approaches will likely be necessary to yield real successes. Thus, meta-analyses of data from individual smoking cessation trials will become crucial and will be facilitated by standardized trial designs, assessments, and outcomes and harmonizable measures. To foster increased collection of high-quality genetics data in clinical trials, we discuss (1) genetically informed trial design, (2) biological samples (collection requirements, storage, and analysis with a focus on genomic data) and genetics consortia, (3) participant consent and data sharing requirements for Institutional Review Board (IRB) approvals, and (4) information on phenotype characterization and meta-analysis. This work aligns with the objectives of the Precision Medicine Initiative and offers guidance for integrating treatment research and genetics/genomics within the nicotine and tobacco research community. It is intended to promote the collection and genotyping of biosamples in existing subject samples as well as the integration of genetic research elements into future study designs. This article cross-references a companion paper in this issue that reviews current evidence on genetic and epigenetic markers in cessation trials. Implications: This article outlines a framework for the consistent integration of biological data/samples into smoking cessation pharmacotherapy trials, aligned with the objectives of the recently unveiled Precision Medicine Initiative. Our goal is to encourage and provide support for treatment researchers to consider biosample collection and genotyping their existing samples as well as integrating genetic analyses into their study design in order to realize precision medicine in treatment of nicotine dependence.